Bibliometric Analysis of Retirement Planning and Financial Stability - Judijanto, Loso; Coryanata, Isma; Nurhayadi, Willy (Westscience Press, 2025)
This study presents a comprehensive bibliometric analysis of global research on retirement planning and financial stability, using data retrieved from the Scopus database and visualized through VOSviewer. The analysis reveals a multidimensional scholarly landscape structured around key themes such as social security systems, financial behavior, psychological readiness, and health-related factors. Findings indicate a significant shift in research focus over the past decade—from institutional and policy-oriented approaches to individual-centric perspectives emphasizing financial literacy, retirement planning, and investment strategies. Influential authors including Mitchell, Lusardi, and Hershey have shaped the intellectual development of the field through interdisciplinary contributions. The United States dominates both in publication output and international collaboration, although emerging participation from countries such as India and Thailand suggests increasing global interest. The study identifies critical research gaps in digital financial tools, informal employment contexts, and health-retirement linkages, calling for more inclusive and forward-looking studies. These insights offer valuable guidance for researchers, policymakers, and practitioners in designing effective strategies to promote financial security in retirement.